Tradução e adaptação da quality of life scales for nursing home residents para o contexto brasileiro - Oliveira, Gabriel Brassi Silvestre de (Universidade Federal de São Carlos, 2014)
The Homes for the Aged may influence the quality of life (QOL) of the patients. However, there is a paucity of literature on specific instruments that assess the quality of life of older people in these contexts. The aim of this study was to culturally adapt the instrument Quality of Life Scales for Nursing Home Residents for the brazilian context. The scale has 54 items in total and includes eleven domains answered in the form of Likert scale and is used to assess the social and psychological aspects of QOL of patients. It is a methodological research, which followed the steps described in the literature on translation and adaptation of instruments: translation; synthesis of translations; back translation; review by a committee of judges and pretesting. The initial translation was developed by two independent qualified translators who investigated and corrected errors of interpretations and of ambiguous terms in the original language. Both translators and researchers conducted a synthesis of the results of the translations. In the back translation, the consensual translated version of the instrument was again passed into the original language (American English). In the next step, a review by a committee of judges aimed to produce a final version, modified and adapted after review and comparison of all translations performed. Likert scale was used for each item of the scale and calculated the Content Validity Index (CVI) in order to produce the final version and adapted. Items that had Validity Index (CVI) of 0.80 were reviewed again by experts. In the last step, the pre-test, the instrument was administered to 15 elderly patients in Homes for the Aged in order to confirm understanding, clarity of all questions in this sample. This step was developed in long-stay institutions for the elderly in a city in the state of São Paulo, in 2013. The Quality of Life Scales for Nursing Home Residents was translated and adapted to the brazilian context. The application of the instrument through the sample of institutionalized elderly showed clarity and understanding of all the items of the instrument.
Keywords: Idosos (Saúde); Instituição de longa permanência; Tradução; Estudos de validação; Qualidade de vida; Activities of daily living; Homes for the aged; Translation; Validation studies; Quality of life; CIENCIAS DA SAUDE::ENFERMAGEM